Skip to main content

Advances, Systems and Applications

Journal of Cloud Computing Cover Image

Table 2 Rules for Evaluating the Service Providers Security using Linguistic Form

From: A fuzzy inference system (FIS) to evaluate the security readiness of cloud service providers

Rule Description Rule Description
1 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}H\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}H\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}H\right\rangle \wedge \\ {}\left\langle EC\stackrel{\wedge}{=}H\right\rangle \underset{then}{\to}\left\langle SC\cong H\right\rangle \end{array}} \) 2 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.R\right\rangle \underset{then}{\to}\left\langle SC\cong \left. AV\right\rangle \right.\right.\end{array}} \)
3 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.H\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}\left.H\right\rangle \wedge \right.\right.\right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.H\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left.H\right\rangle \right.\end{array}} \) 4 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.G\right\rangle \right.\wedge \left\langle AC\stackrel{\wedge}{=}\left.H\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.H\right\rangle \right.\wedge \\ {}\left\langle EC\stackrel{\wedge}{=}\left.H\right\rangle \underset{then}{\to}\left\langle SC\cong \left.H\right\rangle \right.\right.\end{array}} \)
5 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. EX\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.H\right\rangle \right.\right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.H\right\rangle \wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.H\right\rangle \right.\underset{then}{\to}\left\langle SC\cong \left.H\right\rangle \right.\end{array}} \) 6 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.R\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.R\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}\left.H\right\rangle \right.\wedge \right.\right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.H\right\rangle \right.\underset{then}{\to}\left\langle SC\cong \left.H\right\rangle \right.\end{array}} \)
7 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.R\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.R\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}\left.R\right\rangle \wedge \right.\right.\right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.H\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left.R\right\rangle \right.\end{array}} \) 8 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.R\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.R\right\rangle \right.\right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.R\right\rangle \right.\wedge \\ {}\left\langle EC\stackrel{\wedge}{=}\left.R\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left.R\right\rangle \right.\end{array}} \)
9 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \left\langle AC\stackrel{\wedge}{=}\left.R\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.R\right\rangle \wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.R\right\rangle \right.\underset{then}{\to}\left\langle SC\cong \left.R\right\rangle \right.\end{array}} \) 10 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \left\langle AC\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.R\right\rangle \wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.R\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left.R\right\rangle \right.\end{array}} \)
11 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.R\right\rangle \underset{then}{\to}\left\langle SC\cong \left. AV\right\rangle \right.\right.\end{array}} \) 12 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \right.\right.\right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left. AV\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left. AV\right\rangle \right.\end{array}} \)
13 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.G\right\rangle \right.\wedge \left\langle AC\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left. AV\right\rangle \right.\wedge \\ {}\left\langle EC\stackrel{\wedge}{=}\left. AV\right\rangle \underset{then}{\to}\left\langle SC\cong \left. AV\right\rangle \right.\right.\end{array}} \) 14 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.G\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.G\right\rangle \right.\right.\wedge \left\langle AU\stackrel{\wedge}{=}\left. AV\right\rangle \wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left. AV\right\rangle \right.\underset{then}{\to}\left\langle SC\cong \left. AV\right\rangle \right.\end{array}} \)
15 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.G\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.G\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}\left.G\right\rangle \right.\wedge \right.\right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left. AV\right\rangle \right.\underset{then}{\to}\left\langle SC\cong \left.G\right\rangle \right.\end{array}} \) 16 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left.G\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.G\right\rangle \wedge \left\langle AU\stackrel{\wedge}{=}\left.G\right\rangle \wedge \right.\right.\right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.G\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left.G\right\rangle \right.\end{array}} \)
17 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. EX\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left.G\right\rangle \right.\right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.G\right\rangle \right.\wedge \\ {}\left\langle EC\stackrel{\wedge}{=}\left.G\right\rangle \underset{then}{\to}\right.\left\langle SC\cong \left.G\right\rangle \right.\end{array}} \) 18 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. EX\right\rangle \right.\wedge \left\langle AC\stackrel{\wedge}{=}\left. EX\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left.G\right\rangle \wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left.G\right\rangle \right.\underset{then}{\to}\left\langle SC\cong \left.G\right\rangle \right.\end{array}} \)
19   20 \( {\displaystyle \begin{array}{l} if\left\langle CP\stackrel{\wedge}{=}\left. EX\right\rangle \wedge \left\langle AC\stackrel{\wedge}{=}\left. EX\right\rangle \right.\wedge \left\langle AU\stackrel{\wedge}{=}\left. EX\right\rangle \right.\wedge \right.\\ {}\left\langle EC\stackrel{\wedge}{=}\left. EX\right\rangle \underset{then}{\to}\left\langle SC\cong \left. EX\right\rangle \right.\right.\end{array}} \)